Parroquias y diezmos en la historiografía medieval española - Cimino, Carla (2014)
This paper analyzes the main debates of Iberian medieval historiography on the issue of tithes and rural churches. The subject has received much attention during the twentieth century and remains essential for analyzing the structure of cathedral lordship, while it is also the starting point for understanding the material reproduction of secular clergy. It is thus necessary to review the most important studies seeking to demonstrate that Iberian scholars were largely influenced by French historiography. Such influence directed the interest of historians towards studying certain aspects of the subject, while abandoning others. We divided the work into three sections that correspond to the development of the historical discipline: legal-institutional studies, classic social history and the work on social organization of space. We seek to explore the achievements and limits of each of the views, to identify problems that remain to be addressed and to highlight the contributions of each of these schools to a renewed study on the subject.